TRENDS IN MANDARIN BUSINESS COMMUNICATION TRANSLATION: A LITERATURE REVIEW - Alvionita Alindra, Devi; Paradida, Yulia Putri (ELT (English Language Teaching Prima Journal), 2024)
The rapid development of the global economy and trade has positioned China as a major power, making Mandarin a strategic communication tool in international business. In this context, the role of translation is crucial in bridging linguistic and cultural differences between business partners. Translating Mandarin business communication requires linguistic expertise and a deep understanding of cultural values, communication styles, and business ethics to convey messages effectively without causing misunderstandings. Additional challenges arise from the abundance of technical terms unique to business, finance, and legal contexts, which demand precise terminology and appropriate adaptation in the target language. This study aims to analyze current trends in Mandarin business communication translation through a literature review, identify effective translation approaches and techniques, and highlight the challenges and role of technology in business translation. The findings of this study are expected to provide insights for practitioners, translators, and academics to better understand the complexities of Mandarin business translation and to support more efficient cross-cultural business interactions.